THE EFFECTIVENESS OF INTERNATIONAL SANCTIONS IN ACHIEVING FOREIGN POLICY GOALS (International Journal of Food and Nutritional Sciences, 2023)
This study explores the effectiveness of international sanctions in achieving foreign policy goals, focusing on key factors that determine their success or failure. International sanctions are a prominent tool in the arsenal of foreign policy, designed to influence the behavior of states and entities by applying economic, diplomatic, and military pressures without resorting to direct military conflict. Sanctions can include economic restrictions, such as trade embargoes and financial freezes; diplomatic measures, such as severing or reducing diplomatic ties; military sanctions, like arms embargoes; and travel restrictions targeting specific individuals. The effectiveness of these measures is influenced by several critical factors. Clear and specific objectives enhance the likelihood of success, as they provide a concrete target for compliance. Broad international support and consistent enforcement are crucial for maximizing impact, as unilateral or poorly coordinated sanctions often fail to achieve desired outcomes. The economic impact on the targeted state, its resilience and ability to adapt, and the potential for unintended consequences also play significant roles in determining the success of sanctions.Case studies, such as those involving Iran's nuclear program, Russia's actions in Ukraine, and North Korea's nuclear ambitions, illustrate the varied outcomes of sanctions. While sanctions have achieved notable successes in some instances, they have also faced limitations and challenges, including the potential for humanitarian impacts and increased resistance from the target. This exploration highlights the complexity of using sanctions as a foreign policy tool and underscores the need for a nuanced and strategic approach to enhance their effectiveness and mitigate adverse effects.